Intra and interhousehold resource allocation and utilization: Insight from SI-FMS baseline surveys in Malawi and Ghana - Tufa, Adane H.; Kanyamuka, Joseph; Manda, Julius; Kotu, Bekele Hundie; Ziblila, Rashida C.; Webber, Hope (International Institute of Tropical Agriculture, 2023)
Focusing on gender, this study describes mixed farming systems using data collected for monitoring, evaluation, learning, and impact assessment (MELIA) from 1268 household heads, 838 spouses, and 2731 plots in Malawi; and 1317 household heads, 1302 spouses, and 4017 plots in Ghana. The study also includes the perception of selected gender norms among household heads and spouses in Ghana. We categorize the households into four gendered types – male-headed households with a spouse (MHHS), female-headed households with a spouse (FHHS), female-headed households without a spouse (FHHNS), and male-headed households without a spouse (MHHNS) for the analysis. Many studies on gender focus on the household heads. Our study uses information from husbands and wives, and female and male household heads with no spouses to see the intra- and inter-household differences in decision-making on resource use and utilization, focusing more on the use of decision-making sustainable intensification technologies in different cultures, religions, and geographical backgrounds.